Aging behavior of commercial and synthesized dental Y-TZP ceramics - Arata, Anelyse; Bastos Campos, Tiago Moreira; Barros Machado, João Paulo; Yoshito, Walter Kenji; Ussui, Valter; de Lima, Nelson Batista; Nisie Tango, Rubens [UNESP]; Ricci Lazar, Dolores Ribeiro (Trans Tech Publications, 2015)
Yttria-stabilized tetragonal zirconia polycrystals (Y-TZP) is used for dental prosthodontics, however, it can present accelerated tetragonal to monoclinic phase transformation in oral environment. The aim of this study was to compare the behavior of a Y-TZP synthesized in laboratory by the coprecipitation method to a commercial Y-TZP, after hydrothermal aging in pressurized reactor (150°C/ 35 hours). The discs were sintered at 1520°C for two hours. The kinetics curve of phase transformation was determined through the data collect by XRD diffractograms treated by the Rietveld method. The experimental and commercial control groups did not present monoclinic phase. After 35 hours of aging, the experimental group presented 69% of monoclinic phase compared to 67% for the commercial group. Scanning electron microscopy and atomic force microscopy images suggested that the commercial group presented heterogeneity of grain size and that the experimental group was more homogeneous. All groups presented superficial degradation process.
Keywords: Coprecipitation; Degradation; Powder synthesis; Rietveld method; Y-TZP